2000
DOI: 10.1046/j.1365-2796.2000.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae in atherosclerosis

Abstract: Abstract. Saikku P (National Public Health Institute, Oulu, Finland). Chlamydia pneumoniae in atherosclerosis (Minisymposium). J Intern Med 2000; 247: 391±396.Chlamydia pneumoniae is currently the infectious agent most often associated with the inflammation found in atherosclerosis. The seroepidemiological association and the actual presence of pathogen in lesions has been confirmed in numerous studies, in which technical difficulties seem to be the only limitation. Besides animal experiments and intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 63 publications
0
35
0
1
Order By: Relevance
“…Since the interaction in the risk for EH of one allele of the HLA system (a key element of the immune response) and an infectious agent (C. pneumoniae) has been described in our study, the probability that immune and inflammatory mechanisms are important factors in the pathogenesis of EH (as has been well documented in atherosclerosis at the cellular 21 and biochemical level 22 ) is clearly higher than that previously suspected. On the basis of several experimental findings, [23][24][25][26][27][28] it has been hypothesized that chronic C. pneumoniae infection of the vessels may induce a chronic immune response orchestrated by cytokines and mediated by reactive oxygen intermediates. This may result in increased vascular resistance and lead to increased blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Since the interaction in the risk for EH of one allele of the HLA system (a key element of the immune response) and an infectious agent (C. pneumoniae) has been described in our study, the probability that immune and inflammatory mechanisms are important factors in the pathogenesis of EH (as has been well documented in atherosclerosis at the cellular 21 and biochemical level 22 ) is clearly higher than that previously suspected. On the basis of several experimental findings, [23][24][25][26][27][28] it has been hypothesized that chronic C. pneumoniae infection of the vessels may induce a chronic immune response orchestrated by cytokines and mediated by reactive oxygen intermediates. This may result in increased vascular resistance and lead to increased blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…49 -51 Such activation of plaque macrophages may reflect chronic infection of the arterial wall, 24,[52][53][54][55][56][57][58][59] or it may be the result of their interaction with oxidized or otherwise-modified lipoproteins. 60,61 To further explore markers of infection in atherosclerosis, we also measured the level of PCT, which was increased in patients with PAD.…”
Section: Erren Et Al Inflammation Cad and Pad 2359mentioning
confidence: 99%
“…Thus, the pathophysiological significance of the slight increase in PCT seen in our patients with PAD is uncertain but may reflect a low-grade inflammatory response, perhaps in response to primary or secondary bacterial infection. 57 It is also possible that the increase in markers of inflammation in atherosclerosis is not a response to infection or modified lipoproteins within the arterial wall but reflects a low-grade primary activation of the immune system. 62 For example, studies by Wick and others have found evidence of inflammatory activity with cellular infiltrates in the arteries of children and young adults before the development of atherosclerosis.…”
Section: Erren Et Al Inflammation Cad and Pad 2359mentioning
confidence: 99%
“…Chlamydia trachomatis in humans is the major causative agent of sexually transmitted genitourinary infections, ocular trachoma, neonatal pneumonitis and the systemic disease lymphogranuloma venereum (Fields & Barnes, 1992 ;Schachter, 1999). Chlamydophila pneumoniae infections are responsible for several respiratory diseases including bronchitis and sinusitis, about 10-15 % cases of community-acquired pneumonia (Pettersson et al, 1997), and it has also been implicated in many other diseases including atherosclerosis and increased susceptibility to HIV infection (Moulder et al, 1984 ;Saikku, 2000 ;Daian et al, 2000 ;Laga et al, 1991 ;Kuo et al, 1995). We have recently described a new approach based on shared conserved insertion and deletions (indels) in various proteins that has proven very useful in identifying main groups within the domain Bacteria and in understanding their relationship to each other (Gupta, 1998(Gupta, , 2000a.…”
Section: Introductionmentioning
confidence: 99%